Quncho: the first popular tef variety in Ethiopia - Assefa, K.; Aliye, S.; Belay, G.; Metaferia, G.; Tefera, H.; Sorrells, M.E. (Informa UK Limited, 2011)
Tef, Eragrostis tef (Zucc.) Trotter, is the main Ethiopian cereal grown on 2.5 million ha annually, and serving as a staple food grain for more than 50 million people. The major constraints in tef husbandry are low productivity (average about 1 t ha21) and lodging. Scientific research on tef began in the late 1950s and over the years a number of improved varieties and management practices have been developed. However, the research outputs have, until recently, been little adopted by farmers. This paper gives an overview of new and impactful technological, institutional and partnership innovation undertaken by Debre Zeit Agricultural Research Centre with a new tef variety called Quncho. Quncho was developed from an intra-specific hybridization between two improved pure line selection varieties (DZ-01-974 and DZ-01-196). The variety DZ-01-974 is high yielding, but because of the seed colour (pale white) its preference by farmers was limited. On the other hand, the variety DZ-01-196 has been popular for its very white seed colour, but its productivity has been relatively low (1.6–1.8t ha21). Hence, a targeted cross to bring together the high- yielding traits of DZ-01-974 with the seed quality of DZ-01-196 was made in 2000. Quncho was then developed as an F2-derived recombinant inbred line (RIL) through a singleseed descent breeding method. Officially released in 2006, the Quncho variety is presently attracting farmers and seed growers.